2005
DOI: 10.1002/bdd.467
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of intravenous torasemide in diabetic rats induced by alloxan or streptozotocin

Abstract: The pharmacokinetic and pharmacodynamic parameters of torasemide were compared after intravenous administration at a dose of 2 mg/kg to diabetic rats induced by alloxan (DMIA) or streptozotocin (DMIS), and their respective control rats. It was reported that torasemide was mainly metabolized via CYP2C11 in rats and the expression and mRNA level of CYP2C11 decreased in DMIA and DMIS rats. Hence, it could be expected that the time-averaged nonrenal clearance (Cl(nr)) of torasemide could be slower in the diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…Torasemide CYP2C11 in rats Significantly slower and comparable intravenous CL NR values of torasemide in DMIA and DMIS rats, respectively [111] Significantly larger 8-h urine output after the intravenous administration to DMIA and DMIS rats [111] 10…”
Section: Amidopyrinementioning
confidence: 99%
See 2 more Smart Citations
“…Torasemide CYP2C11 in rats Significantly slower and comparable intravenous CL NR values of torasemide in DMIA and DMIS rats, respectively [111] Significantly larger 8-h urine output after the intravenous administration to DMIA and DMIS rats [111] 10…”
Section: Amidopyrinementioning
confidence: 99%
“…[109,110] After the intravenous administration of 2 mg/kg torasemide to male Sprague-Dawley DMIA rats on the fourth day, the CL NR (which could have represented their metabolic clearance) became significantly slower (by 27.2%) than that of the controls. [111] This could have been at least partly due to the significantly smaller free fractions of torasemide in the plasma from DMIA rats (3.56 vs 9.57%). [111] The hepatic CL int for the disappearance of torasemide was not measured because torasemide is a drug with a low hepatic extraction ratio in rats (its 'direct' hepatic first-pass effect was found to be 3-4%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown that diabetes may also alter the pharmacokinetic behavior of many drugs [1][2][3] , and these changes are generally associated with alterations in functional proteins, including cytochrome P450s (CYP450s) and efflux transporters, which participate in the absorption, metabolism, distribution and excretion of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Oral anti-diabetic agents, such as chlorpropamide and glibenclamide, are anions at a physiological pH and have potent inhibitory effects on rOat1-mediated PAH uptake 10 , indicating that they are substrates of Oat1. Pharmacokinetic changes of drugs such as acetaminophen, furosemide, and methotrexate have been reported in rat model of diabetes mellitus induced by alloxan or streptozotocin treatment [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%